Types of Sphenoid Sinus Pneumatization among Nepalese Population - Nepal, Pankaj Raj; Karki, Karuna Tamrakar; Rajbanshi, Jagat Narayan (Eastern Green Neurosurgery, 2020)
Background: The sphenoid sinus is a very important route during the surgical procedure for the lesions inside and around the sella tercica. With the aim to evaluate the anatomical variations of these sphenoid sinuses in the Nepalese population, this study was performed. Methods and Materials: This is a Cross-Sectional analytical study with a non-probability consecutive sampling. Patients of all age groups and all gender who underwent a CT scan of head for any reason were collected, excluding the patients whose sella and / or sphenoid sinus was distorted or fractured for various reasons. A recon image of all the CT scans was made, then were classified base on the sphenoid sinus pneumatization and clival extension of the sphenoid sinus. This was done on the midsagittal image of the CT scan of the head in the bone window. Age was presented as mean and standard deviation (SD), and stratification in groups. Gender, types of sphenoid sinus pneumatization, and clival extension were presented in frequencies and percentages. An association of age and gender with sphenoid sinus pneumatization and clival extension were evaluated using Fischer’s Exact test in SPSS 20. Result: The total number of cases enrolled in the study was 58 with a mean age of 41.62 (SD 22.46) years. The most common type of sphenoid pneumatization was a complete sellar type (52%). Similarly, sub-dorsal clival extension (71%) was more common in this study sample followed by other types. There was a significant association of different age categories with the type of sphenoid pneumatization. The conchal type of the sphenoid pneumatization was exclusively seen only in children. Similarly, gender also showed statistically significant association with the sphenoid pneumatization, where males were associated with more complete type and females with more presellar and incomplete type. Conclusion: The prevalence of complete sellar pneumatization and sub-dorsal type of clival extension were the most common findings in the Nepalese population. Conchal type of sphenoid pneumatization is the predominant findings in childhood. More extensive sphenoid pneumatization and clival extension were the significant findings among the male population.